Atheist Hegel? God in the Phenomenology of Spirit - Prendas Solano, Jorge (2025)
This work is the result of research conducted in commemoration of the 250th anniversary of the birth of G.W.F. Hegel. In this context, one of the great works of this thinker is addressed, namely, *The Phenomenology of Spirit*. The author's aim is to explore the limits and possibilities of Hegel's approach to God in the mode of knowledge of Religion. The conclusion intended to be demonstrated is the legitimacy of the so-called "Hegelian atheism," given that the God derived from Hegel's reflections has no relation whatsoever to a personal entity foreign or distant from humanity.